2016
DOI: 10.1177/1533317516680900
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence in Alzheimer’s Disease

Abstract: The present results suggest that the risk of UI is higher in patients with AD than in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The latter also found, similar to our findings, that osteoporosis appears to be associated with Alzheimer's disease. Similarly, Lee et al [43], Swords et al [44], and Rouch et al [45] reported the association of AD with urinary incontinence, hearing loss, and personality disorders. The fact that the AD group consists of more women (69%) than the control group (53%) may explain the higher incidence of osteoarthritis for the AD group [46].…”
Section: Discussionmentioning
confidence: 88%
“…The latter also found, similar to our findings, that osteoporosis appears to be associated with Alzheimer's disease. Similarly, Lee et al [43], Swords et al [44], and Rouch et al [45] reported the association of AD with urinary incontinence, hearing loss, and personality disorders. The fact that the AD group consists of more women (69%) than the control group (53%) may explain the higher incidence of osteoarthritis for the AD group [46].…”
Section: Discussionmentioning
confidence: 88%
“…As AD progresses, patients decline in both cognitive and physical abilities such as memory loss, changes in personality, confusion, and inability to complete daily tasks such as toileting (Jung et al, 2017). These progressing impairments caused by AD can lead to an increasing risk of UI as it is difficult to identify when or where to void and patients' ability to access the toilet becomes difficult (Lee et al, 2017). It is challenging to accurately assess UI in patients with cognitive and physical deterioration.…”
Section: Behavioral Effects Of Alzheimer's Disease On Urinary Incontinencementioning
confidence: 99%
“…It is estimated that there are 35 million people living with dementia globally and by the year 2030, that number is predicted to double (Lee et al, 2017). Alzheimer's disease (AD) accounts for more than 80% of elderly dementia patients (Jung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the urinary tract deserves mention. New culture techniques have identified diverse microbial communities in healthy urinary tracts , and urinary dysfunction is a prominent feature of PD, AD and MS . As with other systemic infections, urinary tract infection is a key driver of delirium and cognitive decline in the elderly with PD and AD , and is a trigger for MS relapse .…”
Section: Other Microbiomesmentioning
confidence: 99%